Opening up to Native Speaker Norms: The Use of / I / in the Speech of Canadian French Immersion Students - Nadasdi, Terry; Vickerman, Alison (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2017)
Our study examines the extent to which French immersion students use lax /ɪ/ in the same linguistic context as native speakers of Canadian French. Our results show that the lax variant is vanishingly rare in the speech of immersion students and is used by only a small minority of individuals. This is interpreted as a limitation of French immersion students’ sociolinguistic competence. Within the group of students who do use both variants, we document a positive correlation between female and middle-class students and use of the lax variant and suggest these speakers are generally more sensitive to sociolinguistic variation. A reverse correlation between English cognates and laxing was found. This is taken as evidence that the learning of laxing is lexically mediated.